Gaya pembelajaran pelajar sekolah menengah teknik - Abd Razak, Sarimah; Hamzah, Ramlah; Abu, Rosini; Kasa, Zakaria (Universiti Putra Malaysia Press, 2008)
Learning style plays an important role in teaching and learning. Learning style consists of distinct behaviour acting as an indicator on how students learn and adapt from the environment and how students’ mind operate. The purpose of the study was to identify technical secondary schools students’ learning styles. Descriptive research design was used for this study. The sample comprised 635 technical secondary schools students who were chosen using a multistage procedure. The findings showed that majority of Civil, Mechanical, and Electric and Electronic Engineering students were accommodator and converger. For Commerce and Agricultural Science students, they were accommodator, converger and assimilator. The study recommends that teachers should use instructional strategies that accomodate their students’ learning style.